Protocolos anestésicos en cesáreas para pacientes caninas ASA I mediante TIVA - Rocha Pazmiño, Iván André (2021)
A documentary research was carried out with the objective of generating information on the anesthetic protocols in caesarean sections in ASA I canine patients using TIVA. The research was of a bibliographic documentary type, applying to its deductive research bases from premises raised with well-founded precedents, for this it was necessary to collect and review data using sources such as scientific articles, degree papers, blogs including books published on the web. , that have issues related to anesthetic protocols in caesarean sections in ASA I canine patients using TIVA. The collection of information was carried out between the months of August and September of the year 2021. This bibliographic research allowed to demonstrate that the proper use of anesthetics used in ASA I canine caesarean sections both in the intraoperative and post-operative stages has a fundamental function for the both physical and emotional health of the patient and her offspring, since a correct transition from anesthesia can guarantee an effective and safe recovery.